PENGARUH SEX RATIO AYAM ARAB TERHADAP FERTILITAS, DAYA TETAS, DAN BOBOT TETAS - Widi Astomo; Dian Septinova; Tintin Kurtini (JURNAL ILMIAH PETERNAKAN TERPADU, 2016)
This study aimed to determine (1)  This effect of sex ratio arabic chicken on fertility, hatchibility , and doc weight and (2) to determine the best sex ratio of effect arabic chicken on fertility, hatchability, and doc weight.  This study was conducted in August 2015 at Tegalrejo village, Gadingrejo districk, Pringsewu regency.The research use 144 arabic chicken consisted of 18 males and 126 females.  This research use the complete randomized design with 3 treatments and 6 times replications.  Every treatments use 8 of the arabic chiken eggs.  The average of hatching egg weight is 42,96 ± 3,5g.  The result shown that sex ratio effect is not significant (P>0,05) to fertility, hatchability, and doc weight arabic chicken. Keywords : Sex Ratio. Arabic Chicken, Fertility, Hatchability, Hatching Weight